Dynamic characteristics of damage and healthy for fiberglass reinforced epoxy using operational modal analysis / Haizuan Abd. Rahman - Abd. Rahman, Haizuan (2014)
Composite materials with nonlinear properties are proned to subsurface damages.Even though vibration response as damage detection method is widely used in engineering applications, its usage is to nonlinear and nonhomogenous properties especially in composite materials is still limited. This study attempts to apply vibration using Operational Modal Analysis (OMA) on fiberglass reinforced epoxy plate. OMA is used on undamaged fiber glass reinforced epoxy plate to extract the modal parameters and after which the procedure is extended to damage fiberglass reinforced epoxy plate. Both healthy and damaged composite material are tested for different boundary conditions i.e. free-free on 4 edges, 1 edge clamped, 2 edges clamped, 3 edges clamped and 4 edges clamped condition. Then result of frequency from OMA was compared analytically with finite element method. Nastran software is employed in this study. Based on the results, it shows that a high deviation between OMA and finite element method can be observed. Result of frequency from OMA was then compared with Experimental Modal Analysis (EMA) to validate the effectiveness of OMA method. It is shown that results obtained from OMA are equivalent with results obtained from EMA. Results of modal parameters obtained OMA was then compared between healthy and degrees of damaged (1st degree, 2nd degree and 3rd degree of damaged specimen 1 and specimen 2) specimen plates to detect damage using changes of modal parameters. Based from this comparison, it was found that frequency, mode shape and damping can be used to detect damage in fiberglass reinforced epoxy.